EFFECT OF SOWING DATES ON GROWTH, PHENOLOGY AND AGRO METEROLOGICAL INDICES FOR MAIZE VARIETIES - SULOCHANA,; N. S. SOLANKI,; J. S. DHEWA,; R. BAJIA, (The Bioscan, 2015)
An experiment was conducted during Kharif season of 2013 at the Instructional Farm, Rajasthan College of Agriculture, MPUAT, Udaipur to evaluate the effect of sowing dates on growth indices, phenology and agro meterological indices for different maize varieties. Treatments consist of three dates of sowing (June 15, June 30 and July 15) with five maize varieties (HQPM-1, PEHM-2, Pratap Makka-5, Pratap QPM-1 and BIO-9637). The experiment conducted in Split Plot Design (SPD) with four replications. The crop sown on June 15 required significantly higher number of days and accumulated GDD to attain various phenophases compared to June 30 and July 15 sown crops. Higher heat use efficiency, dry matter accumulation and LAI were recorded with the crop sown on June 30 and decreased with delay in sowing. June 30 sown crop recorded grain yield (50.87 q ha- 1) significantly higher under June 15 and July 15 sown crops. BIO-9637 required maximum accumulated growing degree days (GDD) to attain different phenological stages of maize except knee high stage. Among the varieties, BIO-9637 recorded grain yield (51.78 q ha-1) significantly higher over HQPM-1, PEHM-2, Pratap QPM-1 and Pratap Makka-5.